A Study of Mudaraba Financing in Indonesia: The Effect of Temporary Shirkah Fund, Return on Asset (ROA), Financing to Deposit Ratio (FDR) - Asiyah, Binti Nur; Aidiawati, Ria; Wahyudi, Amin; Azis, Ishan; Qurratulaini, Intan (Universitas Negeri Surabaya, 2021)
This article discusses the decline of distribution of mudaraba financing from 2017 to 2019 in a sharia bank in Indonesia, which impacted asset productivity. This study intends to examine the effect of Temporary Shirkah Funds, and Financing to Deposit Ratio on Mudaraba Financing. This study uses a quantitative approach, especially associative research. The sampling technique is non-probability sampling, and the data analysis is multiple regression. The results of this study indicate that (1) Temporary Shirkah Funds have a positive and significant effect on Mudaraba Financing; (2) Return on Assets has a positive and significant effect on Mudaraba Financing; (3) The Financing to Deposit Ratio has a positive and significant effect on Mudaraba Financing; (4) simultaneously Temporary Shirkah Funds, Return on Assets, Financing to Deposit Ratio have a positive and significant effect on Mudaraba Financing. The practical implication of this research is that Islamic banks prioritize Mudaraba Financing to be in line with increasing Murabaha Financing.